Pretreatment And Iiydrolysis Of Rice Straw And Fruits Peel Waste By Using Vermiwash For Bioethanol Production - Md. Nasir, Siti Norfariha (2016)
The main objective for this study was to produce ethanol from lignocellulosic biomass which are rice straw and fruit waste peel (equal ratio of papaya, pineapple and guava). Vermiwash was used in the hydrolysis process. The experimental works involved were biomass characterization, bacteria isolation from venniwash and biochemical tests such as (carboxymethylcellulase) CMC test, starch test and phenol red test, including bacterial identification using 16S rDNA. Besides ethanol concentration, reducing sugar and enzymatic activity determination by dinitrosalicylic acid (DNS) method were also carried out. The study involved the screening part and also the optimization for the factors involved in the ethanol yield using Response Surface Methodology (RSM) and Analysis of Variance (ANOVA). Four